Uncoupling Protein 2 Inhibits Myointimal Hyperplasia in Preclinical Animal Models of Vascular Injury. Issue 10 (12th October 2017) - Zhang, Yan; Zhang, Yaolei; Li, Wei; Wang, Peijian; Gu, Rui; Feng, Yaxing; Wei, Shujie; Peng, Ke; Zhang, Yunrong; Su, Linan; Wang, Qiang; Li, De; et al.
Abstract : Background: Intracoronary stent restenosis, characterized by excessive smooth muscle cell (SMC) proliferation and myointimal hyperplasia, remains a clinical challenge. Mitochondrial membrane potential has been linked to the proliferative rate of SMCs. This study aimed to screen a critical gene regulating mitochondrial potential and to confirm its effects on myointimal formation in preclinical animal models. Methods and Results: We performed transcriptome screening for genes differentially expressed in ligated versus unligated mouse carotid arteries. We observed that uncoupling protein 2 gene ( Ucp2 ) mRNA, encoding UCP2, was transiently upregulated during the first 3 days after ligation and then significantly downregulated from day 7 through day 21, during which time neointima formed remarkably. The UCP2 protein level also declined after day 7 of ligation. In ligated carotid arteries, Ucp2 −/− mice, compared with wild‐type littermates, exhibited accelerated myointimal formation, which was associated with increased superoxide production and can be attenuated by treatment with antioxidant 4‐hydroxy‐2, 2, 6, 6‐tetramethyl‐piperidinoxyl (TEMPOL). Knockdown of UCP2 enhanced human aortic SMC migration and proliferation that can also be attenuated by TEMPOL, whereas UCP2 overexpression inhibited SMC migration and proliferation, along with decreased activity of nuclear factor‐κB. Moreover, nuclear factor‐κB inhibitor attenuated UCP2 knockdown‐enhanced SMC proliferation. Adenovirus‐mediated overexpression of UCP2 inhibited myointimal formation in balloon‐injured carotid arteries of rats and rabbits and in‐stent stenosis of porcine coronary arteries. Moreover, UCP2 overexpression also suppressed neointimal hyperplasia in cultured human saphenous vein ex vivo. Conclusions: UCP2 inhibits myointimal hyperplasia after vascular injury, probably through suppressing nuclear factor‐κB–dependent SMC proliferation and migration, rendering UCP2 a potential therapeutic target against restenosis.